Is the Risk of Myocardial Infarction in People With Human Immunodeficiency Virus (HIV) Associated With Atazanavir or Darunavir? A Nested Case-Control Study Within the French Hospital Database on HIV. (11th December 2019) - Costagliola, Dominique; Potard, Valérie; Lang, Sylvie; de Castro, Nathalie; Cotte, Laurent; Duval, Xavier; Duvivier, Claudine; Grabar, Sophie; Mary-Krause, Murielle; Partisani, Marialuisa; Ronot-Bregigeon, Sylvie; Simon, Anne; et al.
Abstract: Background: The Data Collection on Adverse Events of Anti-HIV Drugs (DAD) study has reported an increased risk of cardiovascular diseases in people with human immunodeficiency virus who were exposed to darunavir (DRV) but not to atazanavir (ATV). Our objective was to evaluate associations between ATV or DRV exposures and the risk of myocardial infarction (MI) in a nested case-control study within ANRS-CO4 French Hospital Database on HIV (FHDH). Methods: Cases were individuals who had a first validated MI between 2006 and 2012. Up to 5 controls were selected at random with replacement among individuals with no history of MI, followed at the time of MI diagnosis, and matched for age and sex. Conditional logistic regression models were used to adjust for potential confounders (MI risk factors and HIV-related parameters) and for cumulative exposure to each antiretroviral drug (ARV). Results: Overall, 408 MI cases and 1250 controls were included: 109 (27%) cases and 288 (23%) controls had been exposed to ATV, and 41 (10%) cases and 107 (9%) controls had been exposed to DRV. There was no significant association between exposure to ATV (adjusted odds ratio [OR] = 1.54; 95% confidence interval [CI], .87–2.73) or DRV (adjusted OR = 0.51; 95% CI, .11–2.32) and the risk of MI. Conclusions: In FHDH, exposures to ATV or to DRV were not significantly associated with the risk of MI, adjusting for complete ARV history, contrary to the analysis in DAD. Abstract : A case-control study nested in the French Hospital Database on HIV found no significant association between exposure to atazanavir or to darunavir and the risk of myocardial infarction in PWH.